EFEKTIFITAS PUPUK NPK LAPIS NANO KITOSAN TERHADAP PELEPASAN UNSUR HARA NITROGEN PADA TANAMAN SAWI PAKCOY - Soekamto, Muhammad Bagus Bima; Purwadi, Purwadi; Mindari, Wanti (Fakultas Pertanian, Universitas Janabadra, 2023)
Slow Release Fertilizer (controlled release fertilizer) is a type of fertilizer with the release of nutrients that can be adjusted to the needs of a plant. Fertilizer that is coated with a semi-permeable material will not dissolve easily in water so that the fertilizer that has been coated is not easily washed off or evaporated. One of the semipermeable materials is chitosan, chitosan is later added to coat a nutrient which will be applied to the soil to absorb and keep the nutrients available and not wasted into the environment. Purpose of this study was to determine the effectiveness of chitosan-coated NPK fertilizer on nitrogen release and interactions with mustard greens. Method used Chitosan-coated NPK fertilizer was given according to the dosage set for each treatment and the results showed that the release of nitrogen elements from chitosan-coated urea fertilizer into the soil proved that nutrients were released more slowly, and conclusions obtained from research There is a real interaction in the treatment of chitosan against Nitrogen in plants. The suggestion from the researcher is based on the need to analyze other parameters to support the completeness of the research on the use of chitosan.Key-words: Chitosan, Slowrelease, PlantINTISARIRendahnya kandungan unsur N dapat menghambat pertumbuhan suatu tanaman dan menyebabkan pertumbuhan tanaman menjadi kerdil, jumlah anakan atau percabangan menjadi sedikit. Oleh sebab itu maka diperlukan penambahan bahan yang dapat mengontrol pelepasan nitrogen pada pupuk sebagai upaya meningkatkan ketersediaan Nitrogen bagi tanaman. Penelitian ini dilaksanakan pada tanggal 05 Desember 2022 hingga tanggal 20 Maret 2023 bertempat di Lahan Green House Institut Teknologi Sepuluh November Surabaya. Penelitian ini menggunakan Rancangan Acak Lengkap 2 faktorial. Faktorial pertama yaitu grade NPK dan factorial kedua dosis penggunaan kitosan. Hasil penelitian menunjukkan bahwa penggunaan kitosan mampu memperlambat proses pelepasan unsur hara pada tanah, berdasarkan hasil sidik ragam terdapat interaksi nyata pada Grade pupuk NPK 20 – 16 – 16 dengan kombinasi kitosan 0,2 gram memberikan hasil yang nyata pada melambatnya unsur hara Nitrogen dibandingkan dengan perlakuan lainnya. Kata kunci: Kitosan, Pelepasan, Nitrogen